Impact of gender on the acceptance of electronic word-of-mouth (eWOM) information in Spain (2018)
The aim of this paper is to explore the differences between males and females in the acceptance of eWOM information. For this purpose, the Information Acceptance Model (IACM), which addresses the characteristics that are evaluated in the use and attitude towards the use of information and play a role in the purchase decision-making process, as demonstrated in the literature, has been used as a reference. An empirical model, which is expected to be validated from the information collected through an online questionnaire completed by 271 users of social networking sites in Spain, has been used. A structural equation model (SEM) is introduced to calculate the measurement structure of the variables and the relationships between them. This paper provides useful insights into the understanding of the differences in the behaviour of males and females regarding online eWOM, and therefore could imply differentiated online marketing and reputation management activities. © 2018 Tautosakos Darbai. All rights reserved.